Increased diabetes risk and interaction with social and medical events in patients upon stroke: Two nationwide studies. (October 2017) - Chu, Lu-Min; Liu, Chih-Chung; Yeh, Chun-Chieh; Chang, Yi-Cheng; Hu, Chaur-Jong; Shih, Chun-Chuan; Cherng, Yih-Giun; Chen, Ta-Liang; Liao, Chien-Chang
Abstract: Background & aims: The relationship between stroke and diabetes is not completely understood. This study evaluated diabetes risk and post-diabetes adverse events in patients with stroke. Methods: We identified 10, 255 adults, newly diagnosed with stroke from 2000 to 2005, using the Taiwan's National Health Insurance Research Database. A comparison cohort of 41, 020 adults without stroke was randomly selected from the same dataset, frequency matched by age and sex. Diabetes events from 2000 to 2013 were ascertained from medical claims. Adjusted hazard ratios (HRs) and 95% CIs were calculated for diabetes associated with stroke. A nested cohort study of 33, 437 patients with inpatient care for diabetes between 2008 and 2013 was conducted to calculate the adjusted odds ratios (ORs) and 95% CIs for adverse events after diabetes, in patients with and without stroke. Results: During 489, 561 person-years of follow-up, there were 10, 742 newly diagnosed diabetes cases. The incidence of diabetes for people with and without stroke was 43.9 and 17.8 per 1000 person-years, respectively ( p < 0.0001). Compared to that for people without stroke, the adjusted HR for diabetes was 2.69 (95% CI 2.56–2.82) for stroke patients. The ORs of post-diabetes pneumonia, urinary tract infection, and mortality associated with stroke were 1.35 (95% CI 1.17–1.55), 1.52 (95% CI 1.36–1.70), and 1.71 (95% CI 1.27–2.29), respectively. Conclusions: We provide evidence that the consequences of stroke are not limited to the neurological defect, but evoke diabetes and a plethora of associated medical, psychological and social impacts the physician must be strongly aware of if evaluating and treating stroke patients. Highlights: People with stroke had increased diabetes risk. History of stroke was associated with post-diabetes pneumonia, urinary tract infection, and mortality. Stroke patients' hip facture, epilepsy, and cerebral hemorrhage were risk factors of post-diabetes adverse events.